Effectiveness of decoronation in preserving the spatial dimensions of the alveolar process – review of literature - Shamsa, Sara; Kobylińska, Angelika; Olczak-Kowalczyk, Dorota (Journal of Stomatology, 2016)
Introduction. Ankylosis is a common complication of tooth replantation, following avulsion, and of tooth reposition, following lateral luxation, in children and adolescents. Aim of the study. To assess the effectiveness of decoronation in preserving the spatial dimensions of the alveolar process in patients with post-traumatic ankylosis awaiting implantation and prosthetic treatment. Materials and methods. Literature describing decoronations of permanent incisors with post-traumatic ankylosis was reviewed using PubMed/MEDLINE. Results. Eleven articles met the criteria and were included in the review; they described 100 decoronated teeth in 97 patients. The average patient’s age on the day of trauma was 10.52 years. In 80% of the described teeth, post-traumatic ankylosis resulted from avulsion, in 8% from lateral luxation, and in 12% from intrusion. Infraposition occurred in 64% of the teeth. Decoronation was performed after 3.8 (±2.38) years of post-traumatic observation in patients aged 13.83 (±2.3) years; average post-traumatic observation lasted 2.56 (±2.07) years. Vertical bone apposition occurred in 24% of patients. Conclusions. Decoronation is an alternative to extraction in post-traumatic permanent tooth ankylosis in children and adolescents. The available literature reports are not sufficient to provide conclusive assessment concerning the effectiveness of decoronation in preserving the spatial dimensions of the alveolar process.